Revision of the elusive ant genus Rhopalomastix (Hymenoptera, Formicidae, Myrmicinae) in Thailand based on morphology and DNA barcodes, with descriptions of three new species - Wang, Wendy Y.; Yong, Gordon W.J.; Jaitrong, Weeyawat (European Journal of Taxonomy, 2021)
The actual prevalence and diversity of the elusive Asian ant genus Rhopalomastix Forel, 1900 in Southeast Asia are largely unknown; only two named species were previously known from Thailand. Following substantial newly-collected museum material made available, we used a combined approach based on morphology and complementary DNA evidence to revise the genus in Thailand. Specimens were sorted to putative species by objective clustering of short fragment (313 bp) COI barcodes, after which specimens of each molecular cluster were morphologically examined. With morphology and supporting genetic evidence, we recognize five species of Rhopalomastix in Thailand, including three species new to science: R. impithuksai Wang & Jaitrong sp. nov., R. parva Wang & Jaitrong sp. nov., and R. robusta Wang & Jaitrong sp. nov. Different castes and sexes are described for most species where available. Descriptions of the two extant described species – R. javana Wheeler, 1929 and R. johorensis Wheeler, 1929 – are also revised, taking into account observations from the additional material. A key to Thai species based on the worker caste, with the three new species included, is further provided.